Peringatan Untuk Tidak Murtad Berdasarkan Ibrani 5 : 11-14 - Alfin Susanto Zagoto; Abad Jaya Zega (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This article explores Hebrews 5:11-14 as the main source for understanding the warning against apostasy in the Christian context. Through a text exegesis approach, this article outlines the key messages contained in the article, focusing on the threat of apostasy and the importance of maintaining the faith. In addition, this article also explores the relevance of this warning in the context of modern spiritual life and how this message can provide guidance for people. believe to strengthen and maintain their faith. By detailing the cultural and theological context of Hebrews S-11-14 this article provides deep insight into the urgency of the warning against apostasy and invites readers to reflect on its significance in their personal journey of faith